Find the value of (x - a)³ + (x - b)³ + (x - c)³ - (x - a)(x - b)(x-c) where a + b + c = 3x
Answers
Step-by-step explanation:
Find the value of (x - a)³ + (x - b)³ + (x - c)³ - 3(x - a)(x - b)(x-c) where a + b + c = 3x
➠ a ³ + b³ + c³ - 3abc = (a + b + c) (a² + b² + c² - ab - ac - bc)
➠ If (a + b + c) = 0 then,
➠ a³ + b³ + c³ = 3abc
Here,
Putting the values,
Thus,
(x - a)³ + (x - b)³ + (x - c)³ - 3(x - a)(x - b)(x-c) = 0
Answer:
Given Equation is a + b + c = 3x.
Given (x - a)^3 + (x - b)^3 + (x - c)^3 - 3(x - a)(x - b)(x - c)
Given Equation is in the form of a^3 + b^3 + c^3 - 3abc.
We know that a^3 + b^3 + c^3 - 3abc = (a + b + c)(a^2 + b^2 + c^2 - ab - bc - ca)
= > (x - a + x - b + x - c)[(x - a)^2 + (x - b)^2 + (x - c)^2 - (x - a)(x - b) - (x - b)(x - a) - (x - c)(x - a)]
= > 3x - (a + b + c)[(x - a)^2 + (x - b)^2 + (x - c)^2 - (x - a)(x - b) - (x - b)(x - a) - (x - c)(x - a)]
= > 3x - 3x
= > 0.
Step-by-step explanation:
thanks..